Thyrotropin receptor autoantibody (TRAb) enhance the expression of thyrotropin receptor on mouse brain vascular endothelial cells: in vivo and in vitro: TRAb enhance the expression of TSHR - Liang, Chunfeng; Yang, Haiyan; Huang, Xuemei; Kuang, Yaqi; Deng, Xiujun; Liu, Yuping; Luo, Zuojie (Cellular and Molecular Biology, 2023)
The possibility that thyrotropin receptor (TSHR) expression in non-thyroid tissue is well-documented. However, there is insufficient data on the expression of TSHR in medulla oblongata regions, particularly when focusing on the background of encephalopathy associated with hyperthyroidism. In this study, we explored the expression of the functional TSHR in Graves' disease (GD) mouse cerebral vascular endothelial cells and the effects of thyrotropin receptor autoantibody (TRAb) on its expression. A mouse model of GD was constructed with an adenovirus overexpressing TSHR289. The location and expression of the TSHR gene and protein in vivo were determined via RT-qPCR, Western blot, and immunofluorescence techniques. The effect of TRAb on the expression of functional TSHR in vitro was investigated using bEnd.3 cells. Our results show that medulla oblongata vascular endothelial cells from GD mice expressed higher levels of TSHR compared to control mice. In an in vitro experiment, novel results demonstrated that after treatment with a monoclonal TSHR-specific agonistic antibody (M22), the expression of TSHR on the bEnd.3 cells increased at both the protein and mRNA levels. Furthermore, compared with bEnd.3 cells were treated with IBMX only, those treated with M22 showed increased cAMP production. This study suggested that TSHR is expressed and functionally active in the mouse medulla oblongata and in vitro-cultured bEnd.3 cells and TRAb (M22) increased the expression of TSHR on bEnd.3 cells.